Ki Hajar Dewantara's Learning Concepts & Kadar M. Yusuf's and Its Relevance in The Era of Society 5.0 - Dinata, Syaiful; Achadi , Muh. Wasith (STAI Syaichona Moh. Cholil Bangkalan, 2023)
Learning is a very important component of making humans truly human. Therefore, this study aims to analyze the learning concept of Ki Hajar Dewantara and Kadar M. Yusuf and its relevance in the era of society 5.0. In this study using the library research method, namely research that analyzes written literature in the form of books and scientific journals as the main source, the results of this study indicate that the concept of learning from the point of view of Ki Hajar Dewantara, namely learning is an activity that will provide knowledge and knowledge, thus obtaining safety. and the highest happiness. Whereas from the point of view of Kadar M. Yusuf said that learning is an activity that will produce knowledge and the concept of learning, Kadar M. Yusuf emphasized that learning includes all sensory aspects so that knowledge is obtained, awareness is formed, admiration is formed, and the final estuary is the formation vertical and horizontal piety. The two figures said that learning is all activity that will provide knowledge, and humans can form piety in themselves to achieve the highest safety and happiness. Therefore, the thoughts of Ki Hajar Dewantara and Kadar M. Yusuf regarding the concept of learning are very relevant in the era of society 5.0; this is because the two figures do not reject changes in the world of Education, as long as the activities carried out produce knowledge and knowledge. Furthermore, the existence of technology can facilitate the achievement of learning objectives because the media in learning is growing and not boring. The thoughts of the two figures are not only relevant in the era of society 5.0 but must be implemented and realized in order to provide a good filter for humans to enjoy the era of society 5.0